Evolution of Professional Words and Phrases in Communications and Information Technology - Naran, Amartuvshin (Mongolian Journal of Applied Linguistics, 2025)
As the global community enters the digital era, new concepts continually emerge in the fields of communications and information technology, leading to the constant expansion of specialized terminology and expressions. This study presents a comparative analysis and evaluation of the ways in which the ever-growing digital lexicon has been translated into Mongolian, employing strategies such as lexicalization, semantic adaptation, equivalence, direct borrowing, hybrid word formation, and neologism creation. Furthermore, the historical development of communications and information technology in Mongolia is examined in relation to the sector’s professional terminology and phrases, with corresponding explanations provided.Ulaanbaatar, Mongolia Харилцаа холбоо, мэдээллийн технологийн салбарын мэргэжлийн үг, хэллэгийн хувьсал, хэрэглээ Хураангуй: Дэлхий нийтээрээ цахим эринд шилжсэн энэ үед харилцаа холбоо, мэдээллийн технологийн салбарт шинэ ухагдахуун өдөр бүр шинээр төрж түүнийг нэрлэсэн мэргэжлийн үг, хэллэг байнга нэмэгдэж байна. Цахим орчны үгийн сан тасралтгүй баяжиж байгааг монгол хэлнээ үгчлэх, утгачлах, дүйцүүлэх, шууд зээлдэх, холимог үг бүтээх, шинэ үг бүтээх зэрэг аргаар орчуулсныг харьцуулан судлав. Монгол Улсын Харилцаа холбоо, Мэдээллийн технологийн түүхийг салбарын мэргэжлийн үг, хэллэгтэй нь хамт уялдуулж тайлбарлав. Түлхүүр үг: Харилцаа холбоо, мэдээллийн технологи, мэргэжлийн үг, хэллэг, жаргон, орчуулга